Magnetic Resonance Imaging of Cells Overexpressing MagA, an Endogenous Contrast Agent for Live Cell Imaging - Donna E. Goldhawk; Claude Lemaire; Cheryl R. McCreary; Rebecca McGirr; Savita Dhanvantari; R. Terry Thompson; Rene Figueredo; Jim Koropatnick; Paula Foster; Frank S. Prato (Molecular Imaging)
Molecular imaging with magnetic resonance imaging (MRI) may benefit from the ferrimagnetic properties of magnetosomes, membrane-enclosed iron biominerals whose formation in magnetotactic bacteria is encoded by multiple genes. One such gene is MagA , a putative iron transporter. We have examined expression of MagA in mouse neuroblastoma N2A cells and characterized their response to iron loading and cellular imaging by MRI. MagA expression augmented both Prussian blue staining and the elemental iron content of N2A cells, without altering cell proliferation, in cultures grown in the presence of iron supplements. Despite evidence for iron incorporation in both MagA and a variant, MagA E137V , only MagA expression produced intracellular contrast detectable by MRI at 11 Tesla. We used this stable expression system to model a new sequence for cellular imaging with MRI, using the difference between gradient and spin echo images to distinguish cells from artifacts in the field of view. Our results show that MagA activity in mammalian cells responds to iron supplementation and functions as a contrast agent that can be deactivated by a single point mutation. We conclude that MagA is a candidate MRI reporter gene that can exploit more fully the superior resolution of MRI in noninvasive medical imaging.